Assessing the effect of nonfarm income on the household cooking energy transition in rural China. (15th March 2023) - Liu, Pihui; Han, Chuanfeng; Liu, Xinghua; Teng, Minmin
Abstract: Although the impact of nonfarm income on poverty and welfare has been fully recorded, far less is known about the relationship between nonfarm income and the rural household energy transition. This paper attempts to fill this gap by investigating the causal effect of nonfarm income on the rural household cooking energy transition. Based on nationwide data from the China Family Panel Studies (CFPS) conducted in 2018, we applied a two-stage instrumental variable (IV)-probit model to overcome the endogeneity challenges. The empirical results reveal that nonfarm income has a positive impact on clean cooking energy use. The marginal effect of agricultural income is not linear but U-shaped. After controlling for endogeneity, a 1% increase in annual nonfarm income results in an increase in the probability of clean cooking energy use of 3.9% (p < 0.01). Nonfarm income can contribute to the rural household cooking energy transition by raising overall household income and relaxing liquidity constraints. The effect is more salient for certain households, such as male-headed households and those living in the economically underdeveloped central and western regions. Our findings contribute to extending the scope and depth of energy ladder theory and provide policy implications to accelerate the rural cooking energy transition. Highlights: We examine the effect of off-farm income on rural household cooking energy choices. We apply a two-stage IV-Probit model to overcomes the endogeneity challenges. We find that off-farm income facilitates the transition from dirty to clean fuels for cooking. In rural China, the energy ladder phenomenon is mainly driven by nonfarm income.